The teaching of ethics at KOE, IIUM - Kabbashi, Nassereldeen Ahmed; Shuriye, Abdi Omar; Faris, Waleed Fekry (Eubios Ethics Institute, 2010)
The universities and education face great challenges, most of them directly or indirectly related to science. Technological disasters, environmental degradation and growing social and economic imbalance between rich and poor have led to an increasing mistrust in science, often directed against the development and application of new technologies. This paper describes the Integration of Islamic Input Curriculum (IIIC). It begins by stressing that ethics cannot be separated from morality and Islamic attitudes and that the training of an ethical engineer is a long integrated involved and continuous process throughout the engineering course and not just teaching of ethical guidelines and rules. It describes the five-year from integration of Islamic Input Curriculum at Kulliyyah of Engineering IIUM which integrates Islamic universal values in the scientific, behavioral, and social aspects of engineering teaching. IIIC approach to teaching ethical issues is presented as a practical example of how the curriculum is employed. Most ethical issues are treated as legal issues for which the Law, shariat, provides general guidelines. The paper may have input on how one can increase the young scientistʼs ability to distinguish right from wrong and to take on social and environmental responsibility?